Analisis Rasio Keuangan Pendapatan Daerah Untuk Mengukur Kinerja Pemerintah Studi Kasus Pada Kabupaten Bandung (2017-2022) - Raden Firsa Uladhiya Ulfa; Indri Yuliafitri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Each region is required to be able to manage finances well in order to achieve regional autonomy. This study aims to analyze the financial performance of the Regional Government of Bandung Regency for the 2017-2022 period using a quantitative descriptive research type. The results of this study indicate that Bandung Regency has a ratio of independence in a consultative pattern with an average ratio of 26.8% or low, the ratio of fiscal decentralization is at an average ratio of 18.8% or low, the ratio of PAD effectiveness is at an average ratio 109.5% or very effective, the ratio of the effectiveness of regional taxes is at an average ratio of 113.73% or very effective, the ratio of the effectiveness of regional levies is at an average ratio of 89.6% less effective.